Tourism Development Strategy Based On Local Wisdom In Improving The Welfare Of Local Communities - Herly M. Oematan; Maria Elerina Douk Tunti; Siprianus G. Tefa (Eduvest - Journal of Universal Studies, 2022)
This study aims to formulate a tourism development strategy based on local wisdom in improving the welfare of local communities in the Districts of North Mollo, Central Mollo, South Mollo, and Fatumnasi, South Central Timor Regency, NTT Province. This research is a quantitative descriptive study using questionnaires, observation and documentation as data collection methods. The analytical tool is a SWOT analysis in order to find out internal and external factors that will be strengths and weaknesses as well as opportunities and threats in the development of tourism based on local wisdom. Research respondents consisted of visitors to tourism sites, village officials and local residents in the tourist areas of North Mollo, Central Mollo, South Mollo, and Fatumnasi. The results show that the sub-districts of North Mollo, Central Mollo, South Mollo, and Fatumnasi have internal and external tourism potential, namely local wisdom in the form of beautiful nature and fresh air as well as serving local agricultural products and local home industry products which are processed professionally through MSMEs. -MSMEs that have local characteristics that cannot be obtained by visitors in other areas. This is a differentiating factor with other tourist sites in NTT.